Comparative Trial of Continuous Flow Enteral and Intravenous Fluid Therapy in Horses - Dias, Domingos C. R.; Ribeiro Filho, José D.; Viana, Rinaldo B.; Bittencourt, Thereza C. C.; Dantas, Fernanda T. D. R.; Teixeira, Raffaella B. C.; Di Filippo, Paula A.; Manso Filho, Hélio C.; Alves, Samuel R.; Santos, Paulo V. M.; Moreira, Nadyne S. (Frontiers in Veterinary Science, 2021)
Continuous flow enteral fluid therapy with isotonic and hypotonic enteral electrolyte solutions are as safe and effective as intravenous fluid therapy. The aim of this study was to carry out a comparative assessment between continuous flow enteral and intravenous (IV) fluid therapy in adult experimentally dehydrated horses. Six experimentally dehydrated adult mares were used in a study carried out in a 6 × 3 crossover design, which each animal received three different treatments (isotonic enteral fluid therapy—EsISO, hypotonic enteral fluid therapy—EsHYPO and intravenous fluid therapy with Lactate Ringer Solution—LR IV, all in continuous flow). Solutions were administered at a rate of 15 mL−1.kg−1.h−1 for 8 h, after 36 h of water and food deprivation. Serum and urinary biochemical assessment; urinary volume, pH and specific gravity; and blood gas analysis were measured at −36, 0, 2, 4, 6, and 8 h. The dehydration period (DP) caused discrete hydroelectrolytic and acid base imbalances. The EsISO, EsHYPO and LR IV increased blood volume. Enteral solutions restored the imbalances yielded by the DP and all treatments increased urine volume. Also, the EsHYPO and LR IV showed no effects in acid base balance, while EsISO showed slightly acidifying effect. The present study certifies the efficacy and safety of isotonic and hypotonic continuous flow enteral fluid therapy in comparison to IV fluid therapy in dehydrated horses.